Concepts and methodology in the exhibition "Baixa em Tempo Real" Lisbon-Rio de Janeiro (Cadernos de Sociomuseologia, 2014)
The paper presents the concepts and methodology followed in the exhibition “Baixa in Real Time” organized  by the Department of Museology - University of Lusofona, which was presented at the beginning of 3013 (March to June) in the Millennium Gallery in Lisbon and the Museum of Republic in Rio de JaneiroThe exhibition was oriented towards a look at Baixa which could take into account its present time, in all its complexity. A present time, of renewed life by the repossession of spaces by diverse sectors of society, where the ancient and the modern, within the built memory or the spur of the moment sight, reencounter a spirit for every site, a personal and not transferable value, or simply a place of encounters.The technological dimension and accessibility issues are also addressed as well as the role of exhibitions in the university context but open to the general publicKey words: expography; museology; augmented reality;